Vertical Distribution of Structural Components in Corn Stover - Jane M. F. Johnson; Douglas L. Karlen; Garold L. Gresham; Keri B. Cantrell; David W. Archer; Brian J. Wienhold; Gary E. Varvel; David A. Laird; John Baker; Tyson E. Ochsner; Jeff M. Novak; Ardell D. Halvorson; et al. (Agriculture, 2014)
In the United States, corn (Zea mays L.) stover has been targeted for second generation fuel production and other bio-products. Our objective was to characterize sugar and structural composition as a function of vertical distribution of corn stover (leaves and stalk) that was sampled at physiological maturity and about three weeks later from multiple USA locations. A small subset of samples was assessed for thermochemical composition. Concentrations of lignin, glucan, and xylan were about 10% greater at grain harvest than at physiological maturity, but harvestable biomass was about 25% less due to stalk breakage. Gross heating density above the ear averaged 16.3 ± 0.40 MJ kg−1, but with an alkalinity measure of 0.83 g MJ−1, slagging is likely to occur during gasification. Assuming a stover harvest height of 10 cm, the estimated ethanol yield would be >2500 L ha−1, but it would be only 1000 L ha−1 if stover harvest was restricted to the material from above the primary ear. Vertical composition of corn stover is relatively uniform; thus, decision on cutting height may be driven by agronomic, economic and environmental considerations.